Single-cell transcriptomics in MI identify Slc25a4 as a new modulator of mitochondrial malfunction and apoptosis-associated cardiomyocyte subcluster - Ting Zhou; Jing Pan; Kai Xu; Chenghui Yan; Jing Yuan; Haixu Song; Yaling Han (Scientific Reports, 2024)
Abstract Myocardial infarction (MI) is the leading cause of premature death. The death of cardiomyocytes (CMs) and the dysfunction of the remaining viable CMs are the main pathological factors contributing to heart failure (HF) following MI. This study aims to determine the transcriptional profile of CMs and investigate the heterogeneity among CMs under hypoxic conditions. Single-cell atlases of the heart in both the sham and MI groups were developed using single-cell data (GSE214611) downloaded from Gene Expression Omnibus (GEO) database ( https://www.ncbi.nlm.nih.gov/geo/ ). The heterogeneity among CMs was explored through various analyses including enrichment, pseudo time, and intercellular communication analysis. The marker gene of C5 was identified using differential expression analysis (DEA). Real-time polymerase chain reaction (RT-PCR), bulk RNA-sequencing dataset analysis, western blotting, immunohistochemical and immunofluorescence staining, Mito-Tracker staining, TUNEL staining, and flow cytometry analysis were conducted to validate the impact of the marker gene on mitochondrial function and cell apoptosis of CMs under hypoxic conditions. We identified a cell subcluster named C5 that exhibited a close association with mitochondrial malfunction and cellular apoptosis characteristics, and identified Slc25a4 as a significant biomarker of C5. Furthermore, our findings indicated that the expression of Slc25a4 was increased in failing hearts, and the downregulation of Slc25a4 improved mitochondrial function and reduced cell apoptosis. Our study significantly identified a distinct subcluster of CMs that exhibited strong associations with ventricular remodeling following MI. Slc25a4 served as the hub gene for C5, highlighting its significant potential as a novel therapeutic target for MI.